Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please help me to check convergence of $$\sum_{n=1}^{\infty}\left(\sqrt{1+\frac{7}{n^{2}}}-\sqrt[3]{1-\frac{8}{n^{2}}+\frac{1}{n^{3}}}\right)$$

share|cite|improve this question
up vote 4 down vote accepted

Hint: Consider the Taylor expansion of the summand about $1/n$ for $n$ large:

$$\sqrt{1+\frac{7}{n^{2}}}-\sqrt[3]{1-\frac{8}{n^{2}}+\frac{1}{n^{3}}} \approx \left (1 + \frac{7}{2 n^2} \right ) - \left (1 - \frac{8}{3 n^2} \right ) = \frac{37}{16 n^2}$$

Use the comparison test.

share|cite|improve this answer
So the series converge, right? – Jonny Jan 10 '13 at 11:47
Yes, but why...? – Ron Gordon Jan 10 '13 at 11:47
because $\frac{37}{16n^2} is < 3\frac{1}{n^2}$? – Jonny Jan 10 '13 at 11:49
Because $\sum (1/n^2)$ converges. How familiar are you with this stuff? – Ron Gordon Jan 10 '13 at 11:51
I don't know Taylor expansion... But I'm familiar with comparison test and convergence of $\sum(1/n^2)$ – Jonny Jan 10 '13 at 11:54

(Presumably with tools from Calc I...) Using the conjugate identities $$ \sqrt{a}-1=\frac{a-1}{1+\sqrt{a}},\qquad1-\sqrt[3]{b}=\frac{1-b}{1+\sqrt[3]{b}+\sqrt[3]{b^2}}, $$ one gets $$ \sqrt{1+\frac{7}{n^{2}}}-\sqrt[3]{1-\frac{8}{n^{2}}+\frac{1}{n^{3}}}=x_n+y_n, $$ with $$ x_n=\sqrt{1+a_n}-1=\frac{a_n}{1+\sqrt{1+a_n}},\qquad a_n=\frac{7}{n^2}, $$ and $$ y_n=1-\sqrt[3]{1-b_n}=\frac{b_n}{1+\sqrt[3]{1-b_n}+(\sqrt[3]{1-b_n})^2},\qquad b_n=\frac{8}{n^{2}}-\frac{1}{n^{3}}. $$ The rest is easy: when $n\to\infty$, the denominator of $x_n$ is at least $2$ hence $x_n\leqslant\frac12a_n$, likewise the denominator of $y_n$ is at least $1$ hence $y_n\leqslant b_n$. Thus, $$ 0\leqslant x_n+y_n\leqslant\tfrac12a_n+b_n\leqslant\frac{12}{n^2}, $$ since $a_n=\frac7{n^2}$ and $b_n\leqslant\frac8{n^2}$. The series $\sum\limits_n\frac1{n^2}$ converges, hence all this proves that the series $\sum\limits_nx_n$ converges (absolutely).

share|cite|improve this answer

Update. Compare $$\sum_{n=1}^{\infty}\left(\sqrt{1+\frac{7}{n^{2}}}-\sqrt[3]{1-\frac{8}{n^{2}}+\frac{1}{n^{3}}}\right) $$ with the serie $$ \sum_{n=1}^{\infty} \frac{1}{n^a} $$ for a convenient $a\geq 1$. Note that if $a_n=\left(\sqrt{1+\frac{7}{n^{2}}}-\sqrt[3]{1-\frac{8}{n^{2}}+\frac{1}{n^{3}}}\right)$, $b_n=\frac{1}{n^a}$ and
$$ 0<\lim_{n\to\infty} \frac{a_n}{b_n}<\infty. $$ then $\sum_{n=1}^{\infty} a_n<\infty$ if, only if, $\sum_{n=1}^{\infty} b_n<\infty$.

share|cite|improve this answer
Seems based on a couple of misconceptions (plus possibly some sign errors), starting with the wrong expansion $\sqrt{1+u}=1+\sqrt{u}+o(\sqrt{u})$ when $u\to0$. – Did Jan 10 '13 at 11:57
@did I update my answer. – MathOverview Jan 10 '13 at 11:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.